Axial Ligand Effects on the Mechanism of Ru-CO Bond Photodissociation and Photophysical Properties of Ru(II)-Salen PhotoCORMs/Theranostics: A Density Functional Theory Study - Niq Catevas; Athanassios Tsipis (Molecules)
Density functional theory (DFT) calculations were employed to study a series of complexes of general formula [Ru(salen)(X)(CO)]0/−1 (X = Cl−, F−, SCN−, DMSO, Phosphabenzene, Phosphole, TPH, CN−, N3−, NO3−, CNH−, NHC, P(OH)3, PF3, PH3). The effect of ligands X on the Ru-CO bond was quantified by the trans-philicity, Δσ13C NMR parameter. The potential of Δσ13C to be used as a probe of the CO photodissociation by Ru(II) transition metal complexes is established upon comparing it with other trans-effect parameters. An excellent linear correlation is found between the energy barrier for the Ru-CO photodissociation and the Δσ13C parameter, paving the way for studying photoCORMs with the 13C NMR method. The strongest trans-effect on the Ru-CO bond in the [Ru(salen)(X)(CO)]0/−1 complexes are found when X = CNH−, NHC, and P(OH)3, while the weakest for X = Cl−, NO3− and DMSO trans-axial ligands. The Ru-CO bonding properties were scrutinized using Natural Bond Orbital (NBO), Natural Energy Decomposition Analysis (NEDA) and Natural Orbital of Chemical Valence (NOCV) methods. The nature of the Ru-CO bond is composite, i.e., electrostatic, covalent and charge transfer. Both donation and backdonation between CO ligand and Ru metal centre equally stabilize the Ru(II) complexes. Ru-CO photodissociation proceeds via a 3MC triplet excited state, exhibiting a conical intersection with the T1 3MLCT excited state. Calculations show that these complexes show bands within visible while they are expected to be red emitters. Therefore, the [Ru(salen)(X)(CO)]0/−1 complexes under study could potentially be used for dual action, photoCORMs and theranostics compounds.